Community Interest and Motivation Toward Recreational Sports Participation in Solo Car Free Day Public Space - Puput Eka Bajuri; Yoelis Gutierrez Sosa; Kwena Mosime (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aimed to identify and describe the forms of recreational sports, public interest, community motivation, and the benefits obtained from recreational sport activities through the Car Free Day program on Slamet Riyadi Street, Surakarta. Methodology: This study used a survey method with a descriptive qualitative approach. Data were collected through observation, questionnaires, interviews, and documentation. The sampling technique applied was proportional purposive random sampling involving 70 respondents participating in recreational sports activities at Solo Car Free Day. Data analysis included preparation, tabulation, and interpretation stages. Main Findings: The findings revealed that Solo Car Free Day accommodated various recreational sports such as jogging, cycling, gymnastics, skateboarding, futsal, volleyball, badminton blind, and nunchaku. Community interest and motivation toward recreational sports were categorized as high, supported by chi-square test results exceeding the critical value of 7.81. The program also improved physical fitness, social interaction, recreation, and public participation in healthy lifestyles. Novelty/Originality of this study: This study highlights the utilization of urban road space as a multifunctional public open space for recreational sports through the Car Free Day program. The research contributes new insights into the relationship between public space utilization, community motivation, and recreational sport participation within an urban social and environmental context.